(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
In this paper I propose two parts of “artivism” born in the 21st century: the animalist’s flash mob and the "environmental theatre " of the research collective Dom. I choose as a method of analysis the theory of performance developed by Turner and Schechner in which it is an expressive form, as well as a social analysis tool. I would liketo highlight how these "alliances of bodies" in space (Butler 2017) use aesthetic strategies, reminiscent of agit prop and guerrilla theater (Milohnić 2005; Loewe 2015) and ally themselves to new media becoming smart mobs. The intention of comparing these actions to Dom’s "teatro paesaggio" intends to highlight "the political uses of theater" (De Marinis 2020) because in these "sympoietic" performances (Haraway 2020) the co-creators of the work are the animal, plant and atmospheric forces capable of resizing and relocating the human, an instance it has in common withenvironmental activism.